PENINGKATAN KETERAMPILAN SOSIAL PESERTA DIDIK MELALUI MODEL PEMBELAJARAN DEBAT PADA PEMBELAJARAN PPKN - Renfita Renfita; Bistari Bistari; Tri Utami; Sulistyarini Sulistyarini; Shilmy Purnama (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to improve students' social skills through the application of a debate learning model in the Pancasila and Citizenship Education (PPKn) subject for ninth-grade students at Jasa Mulia Junior High School, Sungai Baru. The social skills developed in this study include the ability to communicate effectively, work together in groups, respect differences of opinion, and resolve conflicts in social interactions. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 18 ninth-grade students at Jasa Mulia Junior High School, Sungai Baru. Data collection techniques were observation, interviews, and documentation. The research instruments used were student social skills observation sheets and teacher activity observation sheets. The results showed that the application of the debate learning model can improve students' social skills. This is evident in the increase in the percentage of students' social skills from 58.33% in the first cycle to 90% in the second cycle. Therefore, it can be concluded that the debate learning model is effective in improving students' social skills in the PPKn subject for ninth-grade students at Jasa Mulia Junior High School, Sungai Baru.